2022
DOI: 10.1002/bit.28241
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of microorganisms within a urinary catheter polymicrobial biofilm model

Abstract: Biofilms are often polymicrobial in nature, which can impact their behavior and overall structure, often resulting in an increase in biomass and enhanced antimicrobial resistance. Using plate counts and locked nucleic acid/2′‐O‐methyl‐RNA fluorescence in situ hybridization (LNA/2′OMe‐FISH), we studied the interactions of four species commonly associated with catheter‐associated urinary tract infections (CAUTI): Enterococcus faecalis, Escherichia coli, Candida albicans, and Proteus mirabilis. Eleven combination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As mixed-species biofilms and polymicrobial infections are much more common in nature [37,146,147], biofilm studies with multiple species should be performed. Clinical isolates from medical devices have shown that biofilm infections are not only due to single species but also to polymicrobial colonization including even copresence of fungi and bacteria [39].…”
Section: State Of the Art Of Biofilm Studiesmentioning
confidence: 99%
“…As mixed-species biofilms and polymicrobial infections are much more common in nature [37,146,147], biofilm studies with multiple species should be performed. Clinical isolates from medical devices have shown that biofilm infections are not only due to single species but also to polymicrobial colonization including even copresence of fungi and bacteria [39].…”
Section: State Of the Art Of Biofilm Studiesmentioning
confidence: 99%
“…There are three main patterns of microbial spatial organization on biofilms that can be observed when FISH is applied ( Figure 1 -II): a) single cell microcolonies, where each species is in separated microcolonies, showing a non-commensal or neutral interactions ( Nielsen et al., 2000 ); b) co-aggregation, where the different species are all mixed and can be found together throughout the biofilm with a cooperative behavior ( Azevedo et al., 2016 ; Allkja et al., 2022 ); and c) the layered organization, where one species can be found in the lower layer of biofilm and the other in the upper layer, which might be related with both cooperative or competitive relations ( Habimana et al., 2010 ; Almeida et al., 2011 ).…”
Section: Fish To Spatially Locate Microorganisms In Biofilmsmentioning
confidence: 99%
“…Concernig the LNA and 2’OMe probes, there are just a few studies regarding their application to biofilms ( Azevedo et al., 2015 ; Azevedo et al., 2016 ; Allkja et al., 2022 ), and even these are limited for the in situ detection and localization of biofilm populations to assess the spatial organization. Despite of negative charge of LNA and 2’OMe probes, all these studies have shown a complete staining of the biofilm sample and a strong fluorescence signal, even in thicker biofilms ( Azevedo et al., 2015 ); it might be possible that the other characteristics (e.g., higher water solubility, more efficient hybridization) of LNA and 2’OMe ( Braasch and Corey, 2001 ; Elayadi et al., 2002 ; Robertson and Thach, 2009 ) are also determinant, assuring an efficient spatial characterization of biofilm populations.…”
Section: Fish To Spatially Locate Microorganisms In Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation